(untitled) (Revista Lusófona de Educação, 2014)
Improvement in the quality of education in science, technology, engineering and mathematics is vital to global competitiveness. The need for more effec- tive schools and the centrality of the teacher’s role in any substantive school improvement plans are well known. Educators, political factions, and policy- makers are engaged in a lively debate as to whether performance pay schemes or more substantial increments across the salary schedule are more likely to motivate teachers to boost student learning outcomes. Neither side questions that some type of financial incentive is necessary for robust results. Since the economy has made local districts less able to provide either type of financial incentive, this study examines whether expensive pay-related motivators are as essential as the current discussion would suggest. It finds that virtually cost- free motivators such as positional respect, positive working environment, per- sonal meaning, job security, and positive challenge may each be more effective in attracting, retaining, and inspiring quality teachers than any restructuring or improvement of financial compensation. Keywords: administration; education; personnel; technology Resumo: Melhorar a qualidade da educação em ciência, tecnologia, engenharia e matemática é vital para a competitividade global. A necessidade de escolas mais eficazes e a centralidade do papel do professor em quaisquer planos de melhoria substancial da escola são bem conhecidos. Educadores, facções políticas e decisores políticos estão envolvidos num intenso debate sobre se são os sistemas de remuneração por desempenho ou aumentos substanciais em toda a tabela salarial que são mais susceptíveis de motivar os professores para melhorar os resultados da aprendizagem dos alunos. Nenhum dos lados questiona que algum tipo de incentivo financeiro é necessário para obter resultados robustos. Uma vez que a economia tem tornado as autarquias locais menos capazes de fornecer qualquer destes tipos de incentivo financeiro, este estudo procurar examinar se os dispendiosos factores de motivação salariais são tão essenciais como parece sugerir este debate. Mostra-se que factores de motivação virtualmente livre de custos, tais como respeito profissional, ambiente de trabalho positivo, realização pessoal, segurança no trabalho e desafio positivo, podem ser mais eficazes para atrair, reter e inspirar professores de qualidade do que qualquer reestruturação ou melhoria de compensação financeira. Palavras-chave: administração; educação; pessoal; tecnologia